2014
DOI: 10.1111/jcpp.12312
|View full text |Cite
|
Sign up to set email alerts
|

Atypical neural responses to vocal anger in attention‐deficit/hyperactivity disorder

Abstract: • Responses to expressions of hostility by others may be altered in children with ADHD because they have difficulties in recognising negative emotions.• In this, the first study of its kind, we used electrophysiological methods to study brain event-related potentials of children with ADHD in response to angry, happy and neutral vocal expressions.• Compared to controls, children with ADHD displayed significant N100 enhancement and P300 attenuation to angry relative to neutral voices.• This pattern of results pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
1
12
0
1
Order By: Relevance
“…Finally, although we assessed both facial identity and facial emotion recognition in the current study, just one task was used to measure emotion recognition. Accordingly, future studies could employ multiple tests of emotion recognition (including vocal emotion processing; Chronaki et al 2014) to provide comprehensive information about emotion recognition deficits in CD probands and their unaffected relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although we assessed both facial identity and facial emotion recognition in the current study, just one task was used to measure emotion recognition. Accordingly, future studies could employ multiple tests of emotion recognition (including vocal emotion processing; Chronaki et al 2014) to provide comprehensive information about emotion recognition deficits in CD probands and their unaffected relatives.…”
Section: Discussionmentioning
confidence: 99%
“…The only ERP study to date using vocal stimuli has shown enhanced N100 and attenuated P300 amplitudes to vocal anger in 6–11-years-old with ADHD in an emotion recognition task using pure prosodic stimuli ( Chronaki et al, 2015a ). The N100 effect persisted after excluding children with comorbid Conduct Disorder.…”
Section: Attention-deficit/hyperactivity Disordermentioning
confidence: 99%
“…Despite the behavioral evidence of emotional prosody discrimination in early childhood, ERP studies in young children have provided surprising results. Although the processing of emotional cues affects early obligatory ERP components (e.g., N1, P2) in adults, no such effects have been observed in children (Chronaki, Benikos, Fairchild, & Sonuga-Barke, 2014;Chronaki et al, 2012). Instead, ERP amplitude difference between angry and neutral prosody have been reported at late latency ranges around 400 ms in infants and children (Chronaki et al, 2012;Grossmann, Striano, & Friederici, 2005).…”
mentioning
confidence: 96%